Perceiving the affordance of interceptability for another - Damle, Samruddhi; Bootsma, Reinoud J.; Zaal, Frank T. J. M. (Frontiers in Psychology, 2025)
Previous research has established that people can make accurate perceptual judgments regarding the affordance of interceptability for oneself. The present study aimed to explore whether people are also capable of perceiving interceptability for another person. Using a manual lateral interception paradigm, we examined whether a group of observers could make perceptual judgments about the affordance of interceptability for a particular individual (the “actor”). We additionally explored the effects of prior training and of partial visual occlusion on the perception of interceptability for the actor. Three groups of 12 observers each viewed the ball-and-paddle kinematics of the actor performing the interception task. Two groups received full vision, whereas one group received partially occluded vision of the screen. Two groups also received prior training on the interception task, whereas one group did not. All observers were required to make verbal judgments (“no”-calls) when they perceived a ball to be uninterceptable for the actor. The frequency and timings of the judgments of the observers turned out to be similar to those of the actor. Analogous task variables characterized the perceptual performance for the observers and actor alike, suggesting that observers were indeed capable of perceiving affordances for the actor. Lastly, we found that neither prior training, nor visual occlusion, had any significant impact on the observers' judgments. We concluded that individuals are capable of perceiving action possibilities for another person, in a comparable way as they would for themselves.